Internet of Things Implementation in Automatic Fish Feeding - Izak Habel Wayangkau,; Dedy Abdianto Nggego,; Chusnul Chotimah,; Nilfred Patawaran, (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
One of the world's fastest-growing food industries is aquaculture. As a result, aquaculture is a successful industry. Lack of care in the preparation of fish feed is a problem for this industry because it leads to the production of low-quality livestock.This study uses the Arduino microcontroller and ESP 8266 to create an automatic fish feeder that can be remotely controlled using a smartphone. Setting the fish's feeding routine is one way to exercise control. The test method used is the experimental method by conducting 5 times the scheduling time test and 10 times the feed weight measurement test.The test results shows that the tool can control a more regular fish feeding schedule. The percentage accuracy of the automatic fish feed scheduling test reaches 100%, while the percentage accuracy of the feed weight measurement test reaches 90%.